Análisis semiótico del logo de TV Agro Digital - Babahoyo - Quilli Toalombo, Ítalo Livino (2022)
In the development of this case study is intended to analyze the content of digital media that develop in relation to the semiotic analysis of the logo of TV Agro Digital Babahoyo, considering that the information that reaches society through these media generates different reactions in the population and awakens or turns off the interest of this. (Martínez, 2018). A logo is a symbol made up of illustrations and words that are related to make known the identity of a company, brand, institution or society. In some situations, the logo is not simply the symbol with which institutions are represented, it is also accompanied by a story that narrates in a way that generates an emotional connection between the client and the brand; The importance of this study lies in being able to make known to the society of Bahia de Bahia a tool that evidences that a semiotic analysis of Tv Agro Digital's logo allows evidencing how it is structured, which communicational characteristics it possesses and, of course, which ones it lacks. As for the methodology, a descriptive study is developed, where the semiotic analysis of the logo of TV Agro Digital Babahoyo is carried out, using the technique of interviewing experts in the area of communication and graphic design, in order to understand the message conveyed by the logo of the selected media.